Dynamic Risk Factors Characterizing Aggressive Sexual Initiation by Female College Students - Carvalho, Joana (Journal of interpersonal violence, 2021)
Past research has supported that community women engage in sexually coercive strategies as a means to initiate sexual intercourse with men. However, at the present state of the knowledge, there is a great lack of scientific information on the psychological characterization of these women. In accordance, the aim of the present study was to characterize the psychopathological and personality profile of a sample of college women reporting sexual initiation by coercive approaches, and to predict membership in the categories of sexually abusive strategies that were used by these women. Findings revealed that 32.7% of women reported to have used some kind of sexually coercive strategy in the past; these women were characterized by the endorsement of more psychopathology symptoms (e.g., depression, anxiety, somatization), and a maladaptive personality style (e.g., neuroticism, impulsiveness, negative trait-affect), in relation to the nonaggressive peers. Also, among the sexually aggressive group, extraversion predicted membership in the category of physical force (i.e., women using physical force to initiate sexual interaction). Findings add to the literature by showing that college women reporting sexually aggressive strategies as a means to initiate sexual intercourse with men present a set of psychopathological and personality features that are qualitatively similar to those features that were previously found to characterize samples of convicted sexual offenders.